Conifer fossil woods from the Santa Marta Formation (Upper Cretaceous), Brandy Bay, James Ross Island, Antarctica - Pujana, Roberto Roman; Raffi, María Eugenia; Olivero, Eduardo Bernardo (Cretaceous Research)
Conifer fossil woods from the Santonian to lower Campanian Santa Marta Formation are anatomically studied in detail. The wood flora is dominated by conifers, mainly Araucariaceae. Conifer fossil woods represent 84% of the samples (26 of 31) of the assemblage. The remaining samples are dicotyledon woods which are not included in this study. Woods are mostly calcified and preservation is often excellent. Fossil woods include three species of Agathoxylon, Phyllocladoxylon antarcticum, Cupressinoxylon hallei and a new species of Cupressinoxylon, C. rotundum Pujana sp. nov. The conifer-dominated forests are consistent with the pollen and macrofloras previously described from sediments of the same stratigraphic unit. This fossil wood assemblage contributes to understand the floristic changes that took place in the Cretaceous forests. Fil: Pujana, Roberto Roman. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales “Bernardino Rivadavia”; Argentina Fil: Raffi, María Eugenia. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Olivero, Eduardo Bernardo. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina